Trimetazidine and Cardioprotection: Facts and Perspectives. (March 2015) - Tsioufis, Konstantinos; Andrikopoulos, George; Manolis, Athanasios
Trimetazidine (TMZ) is a metabolic agent used in cardiology for more than 40 years. Several studies assessed the cardioprotective effects of TMZ in patients with chronic coronary heart disease (CHD) as well as in patients with heart failure (HF). In light of the inclusion of TMZ in the current guidelines on the management of stable CHD, we reviewed the published literature on TMZ, focusing mainly its effects on patients with stable angina and HF. According to the published literature, there is sufficient evidence to support the addition of this agent in the treatment of symptomatic patients with stable angina.